DESIGN OF INFORMATION SYSTEMS IN HEALTH SERVICES HOSPITALS GANDARIA - Hendri Hendri; Susi Wagiyati, Skom, MM (Jurnal Sistem Informasi, 2001)
Today's progress has touched all aspects of life, including aspects of health care. Inorder to provide good health services, and the sooner it is not wrong if it is acomputerized system should be applied. At the hospital Gandaria currently using thesystem as the elderly, which in addition to the registration section in charge ofseeking patient data is also required to make patient data for new patients, then thedata is given to the receptionis to be given the serial numb er checks. However, whenrelatively few patients is not a problem, but problems arise when total patientincreases, so that the registration is required to give fast service and BAUK. For thisKKP writing this writer hope to give a picture of the health service and to helpcomputerize the task dari registration section.